The red funeral in Vladivostok. An account of the funeral of the Russian people killed on July 1st, 1917, when Czecho Slovak, Japanese and British troops seized the Vladivostok Soviet (London)
Publ. by the Workers' Socialist Federation. Repr.: The New Republic.